Genealogy of Power in Sustainable Tourism Development in Mina Wisata Technopark Sleman - Albizzia, Oktarina; Sakina, Aulia Widya; Pangestu, Mulyoto; Wedadjati, Ratna Sesotya (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2022)
This study aims to analyze the parties involved in innovation program and their interests, identifies the parties who benefit and lose, and determine the sustainability of the development of Mina Wisata Technopark Sleman. This research used qualitative methods with Foucaultian’s framework of the genealogy of power or knowledge. The construction of the dynamics of relations and power relations can be seen from the discourse on the power of the actors involved in the management, such as the central and local governments as planners at the executive and driving levels; the company as the main key in the tourism industry; local communities in the development area as program objects; as well as the Lurah and the Village Apparatus as implementation and supervisors of development. The dynamics of developing a mina wisata technopark resulted in the construction that the existence of a management agency was the result of communicative action through a long dialogue process. So, that power or authority can side with the weakest parties to build productive spaces and their networks in order to improve their welfare. Mina wisata technopark must be developed through the active role of the community in making development decisions in an open, democratic, and responsible manner (bottom up planning), trought synergy with all stakeholders.